Imigrantes venezuelanos e sua inserção no trabalho do agronegócio no Rio Grande do Sul: trabalhadores qualificados, dóceis e de baixo custo? - Siso, Nayibel de los Angeles García (2023)
In the last decade, the international migration scenario in Brazil has undergone changes in the number and origin of immigrants. Currently, the vast majority originate from the Global South, especially from Latin American and African countries, where Venezuelans are the most populous nationality. The annual International Migration Observatory (OBMigra) report for the year 2021 reveals that 1.3 million international immigrants lived in Brazilian territory with resident or temporary visas; These figures continue to rise every year, and even more so if refugees and asylum seekers are also added. Migratory networks and the intermediaries of the actors involved seem to have a lot of influence on the migratory phenomenon; in addition to legislation favorable to the entry and stay of international immigrants in Brazil. In turn, the job market shows interest in the insertion of immigrants, where hiring has grown significantly in the last decade, mainly in the industrial sector and agricultural workers. In this scenario, the objective of this dissertation is to analyze how Venezuelan international immigrants enter the social space and the agribusiness labor market in Rio Grande do Sul. It is a qualitative research, of a descriptive and documentary nature, with intentional sampling of a group of Venezuelan migrants in Rio Grande do Sul. Data collection was possible through semi-structured interviews, data from secondary sources and review of bibliography linked to the research categories covered. It is concluded that Brazil, still without a public migration policy, has a network of formal and informal assistance institutions, with strong State action. The actors in these networks activate intermediaries that influence current migratory flows, and end up being fundamental in insertion in the social space and the formal job market, in addition to generating feelings of hope and resilience in the face of the migratory experience. However, the working conditions found in agribusiness fit into the capitalist logic, which seeks cheap, docile and flexible labor, subject to precarious conditions, or type 3d jobs/3p jobs (heavy, precarious and dangerous): very physical effort, long hours, seasonal hiring, low wages; low-skilled positions, tasks that pose a risk to health or safety, combined with the almost non-existence of mediating union actions, and no contact with government bodies. More studies are needed on the insertion of international immigrants as a workforce in Brazilian agribusiness, with sections by region, production sector, occupations and nationality.